Penelusuran Jejak Sejarah Farmasi di Masa Hindia Belanda - Setia Gumilar (Khazanah Multidisiplin, 2023)
Historiografi of Pharmacy in Nederland-Indie Period could being an alternative for historical writing. The Success of writing history is determined by tracing (source) historical traces. This papes aim for looking the traces and see extent pharmaceutical history wrinting can be used as an alternative to historiography. Thus paper uses a historical method consisting of heuristics, critism, interpretation and historiography. The search was carried out in The national Libraty of Republic of Indonesia, The National Archives of The Republic of Indonesia and Online Searches. The traces found were in the form of books, government documents, and magazines. Based on the findings of the traces, the theme who could be the alternative historical pharmacy researches were institutional pharmacy, pharmaceutical researches, pharmacists, organization of pharmacists, drugs, pharmacies and education of pharmacists.